Kesenian Ketoprak Truthuk: Wujud Nyata Perubahan Sosial Masyarakat Kota Semarang - Rahmadhani, Annisa; Achdiani, Yani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Indonesian traditional arts, including Ketoprak Truthuk, have become an integral part of community life in Semarang City, playing an important role in strengthening cultural identity and facilitating social interaction. This article aims to explore the role of Ketoprak Truthuk in influencing social change in Semarang City. The method used in this article is a literature study with data analysis techniques that involve three activities simultaneously: data reduction, data presentation, and conclusion drawing or verification. The results showed that Ketoprak Truthuk is not only a traditional art form, but also a tangible manifestation of the social changes that occur in the community of Semarang City. Through its cultural values, economic contributions, and social roles, Ketoprak Truthuk has helped strengthen the identity of the community, convey unity, and create positive changes in everyday life. These findings underscore that the government, community, and young generation of Semarang City must actively participate in developing and preserving the art of Ketoprak Truthuk. The preservation and development of traditional arts is done in an effort to strengthen cultural identity and encourage good social change amidst the challenges of modernisation and globalisation.